Conselho de classe e diversidade étnico-racial: um estudo de caso de uma escola particular do Sul de Minas - Miguel, Anivaldo Sérgio (2022)
The research proposal is to investigate the silencing, deletion and invisibilities related to ethnic-racial diversity in the deliberative acts of the class council, as well as, in other socioformative spaces, inside a private High School, located in the South of Minas Gerais, Brazil.To this end, qualitative research will be carried out based on the following methodological procedures: semi-structured interviews with three teachers, members of the class council, who teach the respective subjects of Arts, History, Brazilianness and School Management, Documental Research, Bibliographic Survey, and Analysis of contents. The study intersects with the fields of educational policy and the education of ethnic-racial relations. In this case, the definitions, insurgent problematizations in the class council, and ethnic-racial diversity, dialogue with several contributions of knowledge productions inserted in these fields. It is expected that the research findings can contribute to a better understanding of the way that ethnic-racial diversity emerges or is absent from this important instance, related to the effectiveness of the process of construction of democratic management, which is the Class Council.